2022
DOI: 10.1155/2022/6990263
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Mung Bean or Vigna radiata (L.) Wilczek Seeds in Alloxan-Induced Diabetic Mice

Abstract: Introduction. Despite the development of oral hypoglycemic medications, diabetes and its associated complications continue to be significant clinical issues. The purpose of this study was to examine the antidiabetic effects of Vigna radiata (L.) Wilczek seeds in mice that had been given alloxan to cause diabetes. Methods. In Swiss albino mice, diabetes was brought on by a single intraperitoneal injection of the drug alloxan (150 mg/kg). For 14 days, glibenclamide (5 mg/kg) and methanol extract of V. radiata se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Afterwards, the safe dose for the extract was experimented and the findings suggested that any dose under 3000 mg/kg is safe to be used in mice. Similar dose has been also documented in the following study (43). The results of the oral glucose tolerance test (OGTT) indicated that all doses of the plant extract exhibited the capacity to effectively utilize glucose within the body.…”
Section: Discussionsupporting
confidence: 87%
“…Afterwards, the safe dose for the extract was experimented and the findings suggested that any dose under 3000 mg/kg is safe to be used in mice. Similar dose has been also documented in the following study (43). The results of the oral glucose tolerance test (OGTT) indicated that all doses of the plant extract exhibited the capacity to effectively utilize glucose within the body.…”
Section: Discussionsupporting
confidence: 87%
“…In diabetic mice, the methanol extract of V. radiata seeds also restored liver glycogen and insulin levels and controlled lipid profiles, AST, ALT, and glycated haemoglobin, indicating its potential benefits in mitigating some of the effects of diabetes. [13] 2.…”
Section: Antidiabetic Activities Of Mung Beansmentioning
confidence: 99%
“…The antidiabetic properties of Vigna radiata (Mung beans) are shown by their phytochemistry. [3] Several studies that have used extracts from green gram have also confirmed the Mung beans' ability to lower blood glucose levels and regulate insulin resistance.…”
mentioning
confidence: 92%
“…V. pilosa is a climbing herb, 1–3 m long, with tender branches. V. radiata has been reported to have antidiabetic (Amare et al, 2022) and antiviral (Lo et al, 2020) activities. These plants are routinely included in many Ayurvedic formulations used for the treatment of central nervous system disorders, including memory impairment (Dinesh, 2009; Ministry of Health and Family Welfare, 2000; Vagbhatta, 2011).…”
Section: Introductionmentioning
confidence: 99%